A Carbon-Stabilized Austenitic Steel with Lower Hydrogen Embrittlement Susceptibility - Khanchandani, Heena; Zeiler, Stefan; Strobel, Lucas; Göken, Mathias; Felfer, Peter (Steel Research International, 2023)
High-strength steels are susceptible to H-induced failure, which is typically caused by the presence of diffusible H in the microstructure. The diffusivity of H in austenitic steels with face-centered cubic (fcc) crystal structure is slow. The austenitic steels are hence preferred for applications in the hydrogen-containing atmospheres. However, the fcc structure of austenitic steels is often stabilized by the addition of Ni, Mn, or N, which are relatively expensive alloying elements to use. Austenite can kinetically also be stabilized using C. Herein, an approach is applied to a commercial cold work tool steel, where C is used to fully stabilize the fcc phase. This results in a microstructure consisting of only austenite and M7C3 carbide. An exposure to H by cathodic hydrogen charging exhibits no significant influence on the strength and ductility of the C-stabilized austenitic steel. While this material is only a prototype based on an existing alloy of different purposes, it shows the potential for low-cost H-resistant steels based on C-stabilized austenite.
CRIS-Team Scopus Importer:2023-11-03
Keywords: atom probe tomography; austenite stabilizations; diffusible hydrogen; electron backscatter diffractions; hydrogen embrittlements

Additive manufacturing of 3D yttria-stabilized zirconia microarchitectures - Winczewski, J. P.; Zeiler, Stefan; Gabel, Stefan; Maestre, D.; Merle, Benoit; Gardeniers, J. G.E.; Susarrey Arce, A. (Materials and Design, 2024)
The additive manufacturing (AM) of yttria-stabilized zirconia (YSZ) microarchitectures with sub-micrometer precision via two-photon lithography (TPL), utilizing custom photoresin containing zirconium and yttrium monomers is investigated. YSZ 3D microarchitectures can be formed at low temperatures (600 °C). The low-temperature phase stabilization of ZrO2 doped with Y2O3 demonstrates that doping ZrO2 with ≈ 10 mol% Y2O3 stabilizes the c-ZrO2 phase. The approach does not utilize YSZ particles as additives. Instead, the crystallization of the YSZ phase is initiated after printing, i.e., during thermal processing in the air at 600 °C – 1200 °C for one and two hours. The YSZ microarchitectures are characterized in detail. This includes understanding the role of defect chemistry, which has been overlooked in TPL-enabled micro-ceramics. Upon UV excitation, defect-related yellowish-green emission is observed from YSZ microarchitectures associated with intrinsic and extrinsic centers, correlated with the charge compensation due to Y3+ doping. The mechanical properties of the microarchitectures are assessed with manufactured micropillars. Micropillar compression yields the intrinsic mechanical strength of YSZ. The highest strength is observed for micropillars annealed at 600 °C, and this characteristic decreased with an increase in the annealing temperature. The deformation behavior gradually changes from ductile to brittle-like, correlating with the Hall–Petch strengthening mechanism.
CRIS-Team Scopus Importer:2024-04-05
Keywords: 3D printing; Additive manufacturing; Micromechanics; Photoluminescence; Yttria-stabilized zirconia

Exploring the mechanical properties of additively manufactured carbon-rich zirconia 3D microarchitectures - Winczewski, J. P.; Zeiler, Stefan; Gabel, Stefan; Susarrey-Arce, A.; Gardeniers, J. G.E.; Merle, Benoit (Materials & Design, 2023)
Two-photon lithography (TPL) is a promising technique for manufacturing ceramic microstructures with nanoscale resolution. The process relies on tailor-made precursor resins rich in metal–organic and organic constituents, which can lead to carbon-based residues incorporated within the ceramic microstructures. While these are generally considered unwanted impurities, our study reveals that the presence of carbon-rich residues in the form of graphitic and disordered carbon in tetragonal (t-) ZrO2 can benefit the mechanical strength of TPL microstructures. In order to achieve a better understanding of these effects, we deconvolute the structural and materials contributions to the strength of the 3D microarchitectures by comparing them to plain micropillars. We vary the organic content by different thermal treatments, resulting in different crystal structures. The highest compression strength of 3.73 ± 0.21 GPa and ductility are reached for the t-ZrO2 micropillars, which also contain the highest carbon content. This paradoxical finding opens up new perspectives and will foster the development of “brick and mortar”-like ceramic microarchitectures.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 3D printing; Additive manufacturing; Micromechanics; Micropillar compression; Zirconia

High-Throughput Alloy Development Using Advanced Characterization Techniques During Directed Energy Deposition Additive Manufacturing - Sommer, Niklas; Bauer, André; Kahlmeyer, Martin; Wegener, Thomas; Degener, Sebastian; Liehr, Alexander; Bolender, Artjom; Vollmer, Malte; Holz, Hendrik; Zeiler, Stefan; Merle, Benoit; Niendorf, Thomas; et al. (Advanced Engineering Materials, 2023)
In laser-based direct energy deposition (DED-LB) additive manufacturing (AM), wire or powder materials are melted by a high-power laser beam. Process-specific characteristics enable robust in situ fabrication of compositionally graded materials, e.g., through an adaption of powder mass flow from independent hoppers. Based on the high flexibility of this approach, pathways toward multimaterial AM have been unlocked. Obviously, such characteristics enable high-throughput alloy development. However, rapid alloy development demands substantial characterization efforts to assess phase and microstructural evolution. So far, property analysis is considered as the limiting factor for these high-throughput approaches. Herein, the use of high-brilliance X-Ray analysis and subsequent micropillar compression testing are introduced to tackle these challenges. As a proof of concept, their application to a compositionally graded material made from AISI 316L stainless steel and a CoCrMo alloy is presented. The results obtained reveal that X-Ray analysis can be exploited to evaluate process robustness, chemical characteristics, and phase composition within the gradient regions. Moreover, the use of micropillar compression testing provides spatially resolved insights into the mechanical properties of the gradient regions. The combination of both characterization techniques eventually opens pathways toward a robust and time-efficient alloy development using powder-fed DED-LB (DED-LB/P).
CRIS-Team Scopus Importer:2023-04-28
Keywords: additive manufacturing; alloy development; direct energy deposition; in situ characterization

In situ mechanical testing of hard yet tough high entropy nitride coatings deposited on compliant steel substrates - Kuczyk, Martin; Zawischa, Martin; Krülle, Tim; Vollhüter, Jan; Zeiler, Stefan; Leonhardt, Michael; Kaspar, Jörg; Zimmer, Otmar; Göken, Mathias; Leyens, Christoph; Zimmermann, Martina (Thin Solid Films, 2023)
High entropy nitrides are an interesting material class for wear resistant coatings. Their fracture properties and toughness are of particular interest for future application in tool coatings. Therefore, in situ tensile testing and micro-cantilever experiments were performed on (AlCrTaTiZr)N, (AlCrNbSiTiV)N, (HfNbTaTiVZr)N and (AlTi)N coatings inside a scanning electron microscope. Parallel cracks form during tensile testing from which the fracture toughness was determined via a modified Hsueh and Yanaka model. For this the misfit strain between coating and substrate was treated as an unknown parameter and was fitted to the beginning part of the underlying crack density – applied strain curves. The validity of the model was evaluated by comparing the results with fracture toughness values derived via micro-cantilever bending experiments. A good fit between the data could be observed for three out of four tested coatings. The limitations of the underlying analytical model are presented and discussed. The tested high entropy nitride coatings displayed a promising combination of high hardness and fracture toughness.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Fracture toughness; High entropy nitrides; In situ mechanical testing; Micro-cantilever testing; Tensile testing